PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN FINANCIAL INDICATOR TERHADAP KONDISI FINANCIAL DISTRESS (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018) - Neny Sulistyowati; Afifudin Afifudin; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThe purpose of this study is to discuss the regulation of good corporate governance (number of board directors, managerial ownership, number of audit boards) and financial ratios (liquidity, leverage and profitability) to financial distress conditions. The study sample was 24 companies selected using purposive sampling from manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The financial statements have been obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The research method was carried out using quantitative methods with regressionlogistic analysis techniques and also carried out using statistical instruments SPSS 20.0 version. The results of this study indicate that the number of boards of directors is positive for financial distress conditions, managerial ownership does not affect financial distress conditions, institutional ownership does not affect financial distress conditions, the number of audits that are not related to influence of financial distress conditions, liquidity have a positive influence on financial distress conditions, leverage are not related to influence of financial distress conditions, and profitability have a positive influence on financial distress statement.Keywords : the number of board of director, managerial ownership,institutional ownership, the number of audit committee, liquidity, leverage, profitability.